Hope of the of Parents of Primary School Children on Career in a Rural Community of Raozan Upazila, Chattogram - Raffi, Taifa Hazera; Hoque, A M M Ehteshamul; Mahmud, Sayeed; Mazumder, Pranay Kumar; Mukul, Dilruba Nahar; Ruhie, Taskia Hazera; Risa, Saeeda (IAHS Medical Journal, 2024)
Background: Parents always think about the career of their children. They try to guide the children in such way so that they can lead an independent life in future. The social status, educational background, family environment, ambition etc. forms the basis of thinking of the parents for their children. This study was conducted to find out the pattern of hope ot the parents of Primary School Children on career in a rural community of Raozan Upazila, Chattogram District of Bangladesh. Materials and methods: This descriptive type of cross sectional study was conducted during the period February to October 2021. 100 respondents were selected by purposive type of non-probability technique. Face to face interviews were performed for information collection after getting consent. A pre tested mixed type of questionnaire was used. Results: 38% of the parents belonged to age group 31 to 35 years. Mean age of the parents was 25 years. Among them, 15% were of low socio- economic status and only 10% were of upper class. 45% of the parents had ambition that their child would be a doctor, 10% desired for teacher, 5% engineer and 7% as Islamic scholar. 93% parents had choosen Bangla medium school for their children. 65% parents had kept private tutor at home as mentor for their children and same percentage of parents expressed financial problems to provide education for their children, Conclusion: Socio-economic and literacy status of the families as well as monthly income were closely associated with future planning and ambition of the children. IAHS Medical Journal Volume 06(2), December, 2023; 9-12